1999
DOI: 10.1091/mbc.10.8.2745
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast Pob1p, Which Is Homologous to Budding Yeast Boi Proteins and Exhibits Subcellular Localization Close to Actin Patches, Is Essential for Cell Elongation and Separation

Abstract: The fission yeast pob1 gene encodes a protein of 871 amino acids carrying an SH3 domain, a SAM domain, and a PH domain. Gene disruption and construction of a temperature-sensitive pob1 mutant indicated that pob1 is essential for cell growth. Loss of its function leads to quick cessation of cellular elongation. Pob1p is homologous to two functionally redundant Saccharomyces cerevisiae proteins, Boi1p and Boi2p, which are necessary for cell growth and relevant to bud formation. Overexpression of pob1 inhibits ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 57 publications
3
45
0
2
Order By: Relevance
“…Pob1 Physically Interacts with Cdc42 in a GTP-dependent Manner To address the relationship between Cdc42 and Pob1, we first analyzed the localization of both proteins. It had been described previously that both Cdc42 and Pob1 localized to the growing poles and to the division area (Toya et al, 1999;Merla and Johnson, 2000). We found that GFP-A 8 -Cdc42 partially colocalized with Pob1 ( Figure 4A); moreover, CRIB-GFP also colocalized with Cherry-Pob1 ( Figure 4B), suggesting that Pob1 and active Cdc42 interact.…”
Section: Pob1 Is a Multicopy Suppressor Of Cdc42-879 Thermosensitivitsupporting
confidence: 72%
See 3 more Smart Citations
“…Pob1 Physically Interacts with Cdc42 in a GTP-dependent Manner To address the relationship between Cdc42 and Pob1, we first analyzed the localization of both proteins. It had been described previously that both Cdc42 and Pob1 localized to the growing poles and to the division area (Toya et al, 1999;Merla and Johnson, 2000). We found that GFP-A 8 -Cdc42 partially colocalized with Pob1 ( Figure 4A); moreover, CRIB-GFP also colocalized with Cherry-Pob1 ( Figure 4B), suggesting that Pob1 and active Cdc42 interact.…”
Section: Pob1 Is a Multicopy Suppressor Of Cdc42-879 Thermosensitivitsupporting
confidence: 72%
“…Cdc42 interacted with the C-terminal PH-containing region of Pob1 and this interaction was abolished when the PH domain was absent ( Figure 4F). These results indicate that Cdc42 interacts with the PH domain of Pob1 that has been described as essential for its function (Toya et al, 1999). Interestingly, in the two-hybrid assay pob1 ϩ not only interacted with cdc42G12V and cdc42 ϩ but also interacted with the dominant-negative cdc42T17N allele (data not shown).…”
Section: Pob1 Is a Multicopy Suppressor Of Cdc42-879 Thermosensitivitmentioning
confidence: 72%
See 2 more Smart Citations
“…Overexpression of REPS2 inhibits cell growth, causing the host cells to become round and swollen (Toya et al, 1999). In this study, we investigated the protein expression of REPS2 in a series of 120 clinical paraffin-embedded specimens with intact follow-up data.…”
Section: Discussionmentioning
confidence: 99%